1985
DOI: 10.1104/pp.77.3.735
|View full text |Cite
|
Sign up to set email alerts
|

Ribulose Bisphosphate Carboxylase/Oxygenase Content Determined with [14C]Carboxypentitol Bisphosphate in Plants and Algae

Abstract: As is the case with spinach ribulose bisphosphate carboxylase/oxygenase (Rubisco), 1'4qcarboxyarabinitol bisphosphate (CABP) bound to purified Chlorella Rubisco with a molar ratio of unity to large subunit of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…In their model (7), photosynthetic CO2 fixation in the presence of saturating light is limited by the activity of Rubisco,3 when the CO2 concentration is low, while it is limited by the rate of production of chemical energy on thylakoid membranes or ultimately by the rate of RuBP regeneration from PGA, when the CO2 concentration is saturating. Their model has been supported by Badger et al (3), who showed that the concentration of RuBP in bean leaves was much higher than that of the RuBP binding sites of ' (25). PGA was determined by measuring the absorbancy change of NADH in the conversion of PGA to glycerol-P in the presence of phosphoglycerate kinase, glyceraldehyde 3-P dehydrogenase (NAD+), triose-P isomerase, and glycerol-P dehydrogenase (NAD+) (3 In Figure 2, the Km value of the high-CO2 grown cells for DIC Figure 2.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…In their model (7), photosynthetic CO2 fixation in the presence of saturating light is limited by the activity of Rubisco,3 when the CO2 concentration is low, while it is limited by the rate of production of chemical energy on thylakoid membranes or ultimately by the rate of RuBP regeneration from PGA, when the CO2 concentration is saturating. Their model has been supported by Badger et al (3), who showed that the concentration of RuBP in bean leaves was much higher than that of the RuBP binding sites of ' (25). PGA was determined by measuring the absorbancy change of NADH in the conversion of PGA to glycerol-P in the presence of phosphoglycerate kinase, glyceraldehyde 3-P dehydrogenase (NAD+), triose-P isomerase, and glycerol-P dehydrogenase (NAD+) (3 In Figure 2, the Km value of the high-CO2 grown cells for DIC Figure 2.…”
supporting
confidence: 57%
“…The adaptation to low-CO2 conditions is completed a few hours after transferring the cells, grown on high-CO2 concentrations, to air, and is suppressed by protein synthesis inhibitors (12, 13). While several studies report the changes in photosynthetic characteristics (12,13,15,19,21) or changes in carbonic anhydrase levels and Rubisco content (8,18,20,21,23,25) that occur when cells are transferred from high-CO2 to low-CO2 conditions, there has been little information on the regulation of the photosynthetic carbon reduction cycle during this adaptation.In the present paper, we determined Rubisco content, RuBP and PGA concentrations, and photosynthetic activity during adaptation of high-CO2 grown cells of Chlorella pyrenoidosa to growth on air. Based on these results and the apparent ability for RuBP regeneration in high-and low-CO2 grown cells of Chlorella during photosynthesis, some comments are offered on the regulation of photosynthesis in Chlorella.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In normal higher plants, the ratelimiting step of photosynthesis is not RuBPC, under the best conditions at least, while in green algae, one of the rate-limiting steps is this enzyme (21). Since the effect of Cbl supplement on the photosynthetic activity of the Cbl-limited cells is similar to the methionine supplementation, reduction of PSI activity may be due to a deficiency of methionine in the chloroplasts, which is synthesized by a Cbl-dependent system.…”
Section: Resultsmentioning
confidence: 98%
“…During the C02-free treatment with maize, RuBP was increased up to 6-fold, but when CO2 was reintroduced RuBP quickly returned, indicative that the pool size was not as important as its rate of turnover. (4,23) and it will displace any other known inhibitor (19).…”
Section: Discussionmentioning
confidence: 99%